Linguistic Features of Putri Candrawati Hoax News: A forensic Linguistics Study - Afdilla Moulidya; Saragih, Amrin; Natsir, Muhammad (Language Circle: Journal of Language and Literature, 2024)
A hoax is an attempt to trick or mislead readers or listeners into believing anything when the person who created of the hoax news is aware that the news is false. Hoaxes can be identified in a variety of ways, one of which is to evaluate an argument using linguistics, a discourse analysis. The purpose of this research is to examine the linguistic features of Putri Candrawati hoax news, to investigate the realizations in linguistic features of Putri Candrawati hoax news, and to examine the reason of linguistic features of Putri Candrawati hoax news. The data of this research was taken from Putri Candrawati (PC) statement in TV One’s YouTube Channel. The data were analysed by using Lakoff (2004) Women’s Speech theory, ten linguistic features of women's speech are as follows: hypercorrect grammar, extremely polite forms, emphatic stress, avoidance of harsh swear words, lexical hedges or filler, tag questions, increasing intonation on declarative, empty adjective, exact colour terms, intensifier, and hypercorrect grammar. The findings of this research that there were eight out of ten characteristics of women's speech in the linguistic features of Putri Candrawati hoax news. It was found that the most dominant feature used is intensifier (31 utterances), empty adjectives (28 utterances), lexical hedges or filler (20 utterances), hypercorrect grammar (11 utterances), super polite forms (11 utterances), emphatic stress (5 utterances), avoidance of harsh swear words (4 utterances), tag question (4 utterances).  Two characteristics are absent in the interim, exact colour terms and rising declarative intonation.